Examining the Long and Short Run Effect of Young Workers on Macroeconomic Variables: An Application of Panel Autoregressive Distributed Lag Approach - Rizky Wardhana; Vivi Silvia; M. Shabri Abd. Majid (Research Collaboration Community (RCC), 2021)
The purpose of this research is to analyze the linkage between young workers and macroeconomic variables in Indonesia through a cointegration and causality approach. Multivariate causality between these variables. Using ARDL panel regression (Auto-Regressive Distributed Lag) with data from 2005 – 2019 covering 33 provinces in Indonesia. The results showed that the variable government expenditure on education had no effect on young workers in the short and long term, the variable economic growth only had a positive and significant effect on young workers in the long term. The increase in the minimum wage has a significant negative effect on young workers in the short term, and vice versa, it has a positive and significant effect on the long term. The last variable that has an effect is the investment variable which has a negative and significant effect in the short term on young workers. The results of multivariate causality testing between the variables above have the result that young workers have a two-way causal relationship with the minimum wage and have a one-way relationship with government spending on education.